Enhancing Brand Awareness in TikTok: The Impact of Marketing Communication on Social Media Platforms - Segarwati, Yulia; Rakhmaniar, Almadina; Azka, Zahrah; Gunawan, Iwan; Jamaludin, Maun (LifeSciFi, 2023)
Market orientation is crucial for companies in the face of global competition and evolving customer demands, as companies realize the need for continuous adaptation. This research delves into the influence of